Pengaruh Model Pembelajaran Project Based Learning Terhadap Hasil Belajar IPAS Siswa Kelas IV SD Negeri Karangpucung 01 - Febrian, Nicky Damar; Febriyani, Shoimatun; Riyadi, Ilham Rahmani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of the project-based learning model on the learning outcomes of science science students in grade IV of SD Negeri Karangpucung 01. This type of research is quantitative with the type of experimental research. The research design used is pre-experimental design pretest-posttest which includes the preparation, implementation and final stages. The sample of this study is grade IV students of SD Negeri Karangpucung 01 which totals 19 students. Data was collected using the Science and Technology learning outcome test. The data analysis technique used is quantitative data analysis. Based on the results of data analysis on the pretest results, the average score was 49. knowing the results of the average pretest score The researcher provides treatment using a project-based learning model, after which the researcher conducts a posttest with an average score of 79. Data analysis using a t-test conducted using SPSS software version 23. The results of the t-test showed a Sig (2-tailed) value of 0.00 at the level of significance a = 0.05. Therefore, Ho is rejected and Ha is rejected. Therefore, Ho is rejected and Ha is accepted, indicating that the use of the project-based learning model statistically affects students' IPAS learning outcomes. Based on the research results, it shows that there is an effect of project-based learning model on the learning outcomes of IPAS of fourth grade students of SD Negeri Karangpucung 01.